Cameroon : Poverty Reduction Strategy Paper Third Annual Progress Report; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The Joint Staff Advisory Note reviews Cameroon's Third Annual Progress Report on achievements and obstacles in the implementation of the Poverty Reduction Strategy Paper (PRSP). It highlights the substantial improvement of the fiscal position and the strengthening of fiscal management. It indicates that the government has implemented actions to improve governance and strengthen transparency and accountability across the public administration. It describes the progress in fostering the regional integration agenda in the Central African Economic and Monetary Community (CEMAC). It also provides some guidance on the PRSP monitoring.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet